A restorer‐of‐fertility like pentatricopeptide repeat gene directs ribonucleolytic processing within the coding sequence of rps3‐rpl16 and orf240a mitochondrial transcripts in Arabidopsis thaliana. (12th March 2014) - Arnal, Nadège; Quadrado, Martine; Simon, Matthieu; Mireau, Hakim
Summary The pentatricopeptide repeat (PPR) proteins represent a large family of RNA‐binding proteins that have many roles in post‐transcriptional RNA processes within plant organelles. Among the PPR proteins that target plant mitochondria, the restorer‐of‐fertility (Rf) proteins are characterized by their inhibitory action on mitochondrion‐localized cytoplasmic male sterility (CMS) genes in various crop species. Close homologs to known Rfs from radish, petunia, and rice can be identified in most higher plant species and these proteins define the recognized subgroup of Rf‐like (RFL) PPR proteins. In this paper we describe the function of the RFL9 gene from Arabidopsis thaliana, and show that it is associated with ribonucleolytic cleavages within the coding sequences of rps3‐rpl16 and orf240a mitochondrial transcripts in the Col‐0 accession. RFL9 therefore represents an Rf‐like PPR gene that has the potential to compromise the function of an essential mitochondrial gene and whose function is also associated with a mitochondrial orf sharing significant homology with a proven CMS‐causing orf. We observe that RFL9 is active in only a few Arabidopsis accessions genetically close to Col‐0, which supports the idea that the genetic fixation of this gene represents a regional event in the recent evolution of Arabidopsis. Additionally, RFL9 counts among the RFL genes that are probably controlled by short regulatory RNAs, and our results provides a potential explanation for such control, which in the case of RFL9 might have evolved to limit its detrimental effect on rps3 expression.